The Impact of Multidisciplinary Rehabilitation on Depressive Symptoms in Hemodialysis Patients. (May 2018) - Mohammadi-Kalaveh, Shirin; Toulabi, Tahereh; Hasanvand, Shirin; Gholami, Mohammad; Ghasemi, Fatemeh
Depressive symptom is the most frequent psychological problem reported among chronic kidney disease (CKD) patients being treated by hemodialysis. This article evaluates the effectiveness of multidisciplinary rehabilitation on depressive symptoms in hemodialysis patients and clarifies the role of nurses. This quasi-experimental study was done on 30 patients in the hemodialysis center (educational hospital) in 2013. Eight rehabilitation plans were conducted by nurses. Beck Depression Inventory (BDI) was used before and after intervention. Our data were analyzed using descriptive and inferential statistics. Result of this study shows that there was a significant difference between mean depressive symptom score before (36.4 ± 10.9) and after (10.5 ± 3.1) rehabilitation ( p < .001). It is recommended that rehabilitation program be implemented in all hemodialysis centers with the participation of specialists in different fields.